Lived Experience of Breast Cancer Survivors: A Phenomenological Study - Lawot , Isabel; Gharti , Kamala; Singh, Shreejana; Sharma , Mohan R (Journal of Institute of Medicine Nepal, 2023)
Introduction Breast cancer (BrCa) is the most common cancer in women worldwide. The population who survives breast cancer is increasing; even so, they usually have to go through many problems in their life. Except for the diseased part, numerous socio-cultural factors may pose challenges for the survivors. Hence, the aim of this study is to explore the experiences of cancer survivors. Methods A phenomenological qualitative design was performed with eight BrCa survivors in the Kaski district of Nepal. Data were collected through semi-structured in-depth interviews and analyzed using Colaizzi’s descriptive phenomenological method. Results Two major themes were extracted from the in-depth interviews. One was the reaction to the diagnosis and another was fear of disease. Most participants lacked awareness of their cancer diagnosis, and nearly all of them experienced fear that persisted until death. They faced a multitude of physical issues throughout the treatment phase and subsequent years, including headaches, loss of appetite, anemia, gastritis, body pain, and swollen extremities. Additionally, they grappled with psychological challenges such as anxiety and depression, rendering them more susceptible. Financially, due to the exorbitant costs of treatment, they had to resort to borrowing money from others, with the burden primarily falling upon their families Conclusion Most of the participants had fear regarding illness, treatments, recurrence, and death. Patients were worried about the cost of care. Therefore, it is imperative for family members and healthcare professionals to recognize the experiences of breast cancer survivors in order to optimize patient health during critical stages.